The Trick of the Hedgehog: Case Report and Short Review About Archaeopsylla erinacei (Siphonaptera: Pulicidae) in Human Health. Issue 1 (9th October 2019) - Greigert, Valentin; Brunet, Julie; Ouarti, Basma; Laroche, Maureen; Pfaff, Alexander W; Henon, Nicolas; Lemoine, Jean-Philippe; Mathieu, Bruno; Parola, Philippe; Candolfi, Ermanno; Abou-Bacar, Ahmed
Abstract: Fleas are ectoparasites of various animals, including Homo sapiens Linnaeus, 1758 (Primates: Hominidae). Among the species relevant to the human health field, either due to their dermatopathological potential or because of their role as vectors of microorganisms responsible for infectious diseases, such as plague or murine typhus, are the human flea, oriental rat flea, closely related cat and dog fleas, and chigoe flea. However, other species can accidentally infest humans. We have herein reported two unusual cases of humans infested and bitten by Archaeopsylla erinacei, the hedgehog flea. This species has been identified using stereomicroscopy, on the base of key characteristics. Furthermore, a brief literature review has revealed that hedgehog fleas could carry human-infectious agents, such as Rickettsia felis Bouyer et al. 2001 (Rickettsiales: Rickettsiaceae) or Bartonella henselae Regnery et al.1992 (Rhizobiales: Bartonellaceae). Using molecular biology, we thus tested nine A. erinacei specimens taken from these patients, for several bacteria species commonly associated with hematophagous arthropods, implicated in human pathology. However, all our samples were proven negative. The role of A. erinacei in human epidemiology has never been evaluated to date. This report sought to remind us that these fleas can be accidental parasites in humans. In addition, recent findings pertaining to bacteria of medical interest that are present in these insects should be brought to the fore, given that the question of their role as vectors in human infections remains unanswered and deserves further investigation.